Application of Online Learning during the Covid-19 Pandemic through Zoom Meeting at Elementary School - Ganesha, Putri; Nandiyanto, Asep Bayu Dani; Razon, Brando Cabigas (Indonesian Journal of Teaching in Science, 2021)
The Covid-19 disease is not an epidemic that can be ignored, the development of the transmission of this virus is quite significant because its spread is global and all countries are feeling the impact, including Indonesia. The impact of Covid-19 has a very strong impact on education, therefore in the education sector, the government through the Ministry of Education and Culture has implemented a learning from home policy. Online learning is a solution to the implementation of online learning, but we already know that online learning is not as easy as learning as usual or offline learning. In this article, we will discuss online learning using Zoom Meeting. The research method used is a qualitative method with a phenomenological approach and conducting observations and interviews. The obstacles faced are electronic media and internet quotas for online learning. Not all students are equal in terms of economics, which is the only problem.